On the Higher Power Sums of Reciprocal Higher-Order Sequences - Zhengang Wu; Jin Zhang (The Scientific World Journal)
Let {un} be a higher-order linear recursive sequence. In this paper, we use the properties of error estimation and the analytic method to study the reciprocal sums of higher power of higher-order sequences. Then we establish several new and interesting identities relating to the infinite and finite sums.